Competence of Economic Teachers in the Industrial Revolution Era 4.0: Case Study at State High Schools in Malang City, Indonesia - Rachmawati, Dian; Handayani, Sri; Rokhmani, Lisa (KnE Social Sciences, 2020)
The competencies needed by teachers in the era of disruption according to the Ministry of Education and Culture of the Republic of Indonesia include teachers, gatekeepers, facilitators, catalysts, and connectors. This research was conducted in 10 Public High Schools in Malang City. The focus of research is to find out how the level of competency of economic teachers in the era of industrial revolution 4.0. This research is a preliminary research, through preliminary studies and field surveys. From the survey results, it is known that the competences of economic teachers are still focused on teaching, gatekeepers, and some facilitators. Then the training model to improve teacher competences in the industrial revolution 4.0 era will be very helpful. In the next study, the development of teacher competency training era in the Republic of Indonesia 4.0 will be carried out with the aim of increasing teacher competence, which in the long run will improve the quality of students. Keywords: teacher competence, industrial revolution 4.0